Axonal refractory period of single short toe extensor motor units in neuropathies and neuromuscular diseases. Issue 12 (December 1981) - Borg, J
Abstract : Electromyographic recordings were carried out on 36 patients with neuropathies and neuromuscular disorders with a selectivity permitting identification of single motor unit potentials during maximal voluntary effort and after supramaximal nerve stimulation. The axonal conduction velocity and refractory period of 117 motor units were determined and the findings were compared to those in previously studied normal subjects. The axonal conduction velocity spectrum was 15-52 m/s. Fifteen per cent of all motor units had axonal conduction velocities below 30 m/s which is below the normal range. When test stimulus strength was 10% above the axonal threshold at rest the refractory period was 1.88 +/- 0.43 ms which is slightly longer than the corresponding value in healthy subjects (1.67 +/- 0.25 ms). The relationship between the axonal conduction velocity and refractory period observed in healthy subjects did not hold for these patients. Thirty-eight per cent of all motor motor units with axonal conduction velocities within the normal range had refractory periods longer than 2.0 ms which was only infrequently observed in healthy subjects. When test stimulus strength was 50% above the axonal threshold at rest the refractory period was 1.16 +/- 0.42 ms which was significantly longer (p less than 0.02) than in healthy subjects (0.64 +/- 0.21 ms). At this stimulus strength 40% of all motor units with axonal conduction velocities within the normal range had refractory periods above 1.0 ms which was never the case in healthy subjects. The significance of these findings with regard to the clinical application of the Hopf technique for determining the conduction velocity spectrum of peripheral motor nerves is discussed.